Isotopic composition and elemental concentrations in groundwater in the Kuiseb Basin and the Cuvelai-Etosha Basin, Namibia - N. A. Kgabi; E. Atekwana; J. Ithindi; M. Uugwanga; K. Knoeller; L. Motsei; M. Mathuthu; G. Kalumbu; H. R. Amwele; R. Uusizi (Proceedings of the International Association of Hydrological Sciences, 2018)
We assessed environmental tracers in groundwater in two contrasting basins in Namibia; the Kuiseb Basin, which is a predominantly dry area and the Cuvelai-Etosha Basin, which is prone to alternating floods and droughts. We aimed to determine why the quality of groundwater was different in these two basins which occur in an arid environment. We analysed groundwater and surface water for the stable isotope ratios of hydrogen (δ2H) and oxygen (δ18O) by cavity ring-down spectroscopy and metals by inductively coupled plasma mass spectrometry. The δ2H and δ18O of surface water in the Cuvelai-Etosha Basin plot on an evaporation trend below the global meteoric water line (GMWL) and the local meteoric water line (LMWL). The δ2H and δ18O of some groundwater samples in the Cuvelai-Etosha Basin also plot on the evaporation trend, indicating recharge by evaporated rain or evaporated surface water. In contrast, the δ2H and δ18O of groundwater samples in the Kuiseb Basin plot mostly along the GMWL and the LMWL, indicating direct recharge from unevaporated rain or unevaporated surface water. Fifty percent of groundwater samples in the Cuvelai-Etosha Basin was potable (salinity < 1 ppt) compared to 79 % in the Kuiseb Basin. The high salinity in the groundwater of the Cuvelai-Etosha Basin does not appear to be caused by evaporation of water (evapo-concentration) on surface prior to groundwater recharge, but rather by the weathering of the Kalahari sediments. The low salinity in the Kuiseb Basin derives from rapid recharge of groundwater by unevaporated rain and limited weathering of the crystalline rocks. The order of abundance of cations in the Kuiseb Basin is Na > K > Ca > Mg vs. Na > Mg > Ca > K for the Cuvelai-Etosha Basin. For metals in the Kuiseb Basin the order of abundance is Fe > Al > V > As > Zn vs. Al > Fe > V> As > Zn for the Cuvelai-Etosha Basin. The relative abundance of cations and metals are attributed to the differences in geology of the basins and the extent of water-rock interaction. Our results show that the quality of groundwater in Cuvelai-Etosha Basin and Kuiseb Basin which vary in the extent of aridity, is controlled by the extent of water-rock interaction at the surface and in the groundwater aquifer.